Perilaku Belajar Pengunjung di Perpustakaan Bintang Cemerlang Kampung Maredan Barat Kecamatan Tualang Kabupaten Siak - Astrid Labegi; Said Suhil Achmad; Muhammad Jais (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to understand how visitors learned at the Bintang Cemerlang Library in Maredan Barat village in Tualang district, Siak Regency. The methodology used in this study is qualitative descriptive research, which is designed to examine various issues in the field and get meaning based on how the research is carried out, using a qualitative approach, aiming to study and measure the learning behavior of visitors at the Bintang Cemerlang Library located in West Maredan Village, Tualang District, Siak Regency. The results of this study show that there are 9 indicators of learning behavior of library visitors, namely: 1) habits, 2) skills, 3) observation, 4) associative thinking and memory, 5) rational and critical thinking, 6) attitudes (attitudes), 7) inhibition, 8) appreciation, and 9) emotional behavior. The conclusion of this study is that the learning behavior of visitors to the Bintang Cemerlang Library showed good learning behavior. There are 8 indicators, namely 1) habits, 2) skills, 3) observation, 4) associative thinking and memory, 5) rational and critical thinking, 6) attitudes 7) appreciation, 8) emotional behavior that shows good learning behavior from library visitors, and 1 indicator, i.e. inhibition of displaying bad behavior. Keywords: Learning Behavior, Visitors, Libraries